Multi-platform microRNA profiling of hepatoblastoma patients using formalin fixed paraffin embedded archival samples. Issue 1 (December 2015) - Leichter, Anna; Purcell, Rachel; Sullivan, Michael; Eccles, Michael; Chatterjee, Aniruddha
Abstract Background Formalin fixed paraffin embedded (FFPE) samples are a valuable resource in cancer research and have the potential to be extensively used. However, they are often underused because of degradation and chemical modifications occurring in the RNA that can present obstacles in downstream analysis. In routine medical care, FFPE material is examined and archived, therefore clinical collections of many types of cancers exist. It is beneficial to assess and record the quality of data that can be obtained from this type of material. The current study investigated three independent platforms and their ability to profile microRNAs (miRNAs) within FFPE samples from hepatoblastoma (HB) patients. Findings Here we present three types of datasets consisting of miRNA profiles for 13 HB patients with different tumour types and molecular variations. The three platforms that were used to generate these data are: next-generation sequencing (Illumina MiSeq), microarray (Affymetrix® GeneChip® miRNA 3.0 array) and NanoString (nCounter, Human v2 miRNA Assay). The mature miRNAs identified are based on miRBase version 17 and 18. Conclusions These datasets provide a global landscape of miRNA expression for a rare childhood cancer that has not previously been well characterised. These data could serve as a resource for future studies aiming to make comparisons of HB miRNA profiles and to document aberrant miRNA expression in this type of cancer.